New Theory of Malaysian Corporatism – A Prologue for a ‘Different’ Methodology - Mohd Kamal, Khairil Annuar (Universiti Malaysia Sarawak (UNIMAS), 2012)
In this paper I outline a rationale for a general methodology will guide my research on Malaysia Inc and Malaysian Corporatism. The discussion in this paper will serve as a starting point in entering into the specific methodology to come up with a new theory of Malaysian Corporatism – which will be outlined in another paper. For this paper I will deal with the background of my methodology mainly, with a critique of the traditional and conventional way of theory building; and this critique will pave the way for the introduction of the a general methodology of this research. This paper therefore serves as a prologue to a detailed description to a methodology that will lead to the New Theory of Malaysian Corporatism.